THE CORRELATION BEETWEEN MOTHER'S NUTRITIONAL STATUS AND PARITY WITH THE INCIDENT OF LOW BIRTH WEIGHT (LBW) AT A PUBLIC HEALTH CENTER SURABAYA - Hapsari, Fransiska Niken; Astika Gita Ningrum; Muhammad Ardian Cahya Laksana; Widati Fatmaningrum (Indonesian Midwifery and Health Sciences Journal, 2024)
Background: One of the highest causative factors of neonatal death in Indonesia is low birth weight (LBW), around 7,150 (35.3%) cases. Even though the trend of LBW incidents in East Java is decreasing, in the city of Surabaya itself the death rate due to LBW has increased from 31 deaths to 51 deaths. Simomulyo Public Health Center was ranked first with the highest incidence of LBW in Surabaya with 45 cases in 2019. Even though there was a decrease in cases in 2020, the death rate actually increased from 1 death to 4 deaths. WHO (2017) defines LBW as babies born weighing â‰¤ 2500 gr. Nutritional status and parity are two of the many risk factors for LBW. Knowing the causal relationship with the occurrence of LBW is important to do at the public Health Center as a first step in preventing LBW in the future. Method: This research is quantitative with an analytical observational design using a cross-sectional approach. Samples were taken using probability sampling techniques, namely random sampling. The total samples taken were 96 samples. Result: The results of the research was found that there was a relationship between nutritional status and the incidence of LBW with a value of p=0.005 (p<0.05) and the relationship between parity and the incidence of LBW with a value of p=0.001 (p < 0.05). Conclusion: there is a correlation between nutritional status and parity and the incidence of LBW at the Simomulyo Public Health Center Surabaya.